The Impact of prolonged antibiotic use on the development of bacterial resistance - a literature review - Zimonczyk, Mariusz; Zawół, Monika; Nojek, Paweł; Pawlik, Wiktoria; Błaszczyński, Gustaw; Nowotarska, Agnieszka (Journal of Education, Health and Sport, 2024)
Introduction and Objective. Antimicrobial resistance (AMR) arises when pathogens no longer respond to antimicrobials, including antibiotics, making infections harder to treat and increasing the risks of severe illness and death. Although AMR is a natural evolutionary process, human activities, especially the misuse of antimicrobials in healthcare, agriculture, and animal care, accelerate its spread. This review examines the impact of prolonged antibiotic use on bacterial resistance and analyzes global trends and strategies to combat AMR. Methods. A literature review was conducted using PubMed and Google Scholar with search terms like "antimicrobial resistance," "antibiotic-resistant bacteria," and "overuse of antibiotics." Articles from the last five years were prioritized. State of Knowledge. AMR poses a major global health threat due to excessive and improper antibiotic use, resulting in resistant infections and higher healthcare costs. Addressing AMR requires limiting antibiotic use, implementing rapid diagnostics, and exploring alternatives like bacteriophage therapy. Conclusions. Innovative treatments, such as bacteriophages, and rapid diagnostics show promise, while public education on responsible antibiotic use is essential. Combating AMR will require coordinated international efforts, research support, and global standards to maintain effective treatments in the future.